Extraction, purification and analysis of thermal stability of xylose isomerase - Valsange, Anmol; Evarkar, Sarang P; Tawde, Sachin V; Kareppa, Basawraj M; Gujar, Rekha S (Current Botany, 2012)
Thermostable enzymes are the enzymes which active even at high temperatures, such enzymes are industrially as well as biochemically very important. Xylose isomerase (EC 5.3.1.5) is one such enzyme with suitable commercial applications. It is heat stable and does not require expensive cofactors such as NAD or ATP for activity. The microorganisms producing this enzyme were isolated from hot water spring near ‘Surat’. The organisms were isolated and purified by using different screening methods. The isolated organisms were then subjected to optimum growth conditions for enzyme production. This enzyme was then assayed for its thermal stability at elevated temperatures by using DNSA.